2009
DOI: 10.1002/chin.200912209
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Phytotoxic Metabolites from Pestalotiopsis sp. HC02, a Fungus Residing in Chondracris rosee Gut.

Abstract: Two new phytotoxic g-lactones, pestalotines A and B (1 and 2, resp.), along with 4-oxo-4H-pyran-3-acetic acid (3) and 6-hydroxyramulosin ( ¼ 3,4,4a,5,6,7-hexahydro-6,8-dihydroxy-3-methyl-1H-2-benzopyran-1-one; 4), were isolateded from the culture of Pestalotiopsis sp. HC02, a fungus residing in the Chondracris rosee gut. Structures of the new metabolites were elucidated on the basis of their IR, NMR, and MS data. Pestalotines A and B (1 and 2, resp.) significantly inhibited the radical growth of Echinochloa cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Many species of Pestalotiopsis are saprobes, while others are pathogenic or endophytic on living plant leaves and twigs [9]. Some Pestalotiopsis species have gained much attention in recent years as they produce many important secondary metabolites with potential use in medical applications and Cultivations were conducted at 30°C and pH 6.5 in 250-ml Xasks containing 100 ml of YEPX broth without shaking for 72 h. Biomass were measured as dry weight in the control of plant diseases [14,18,26]. No reports showed that Pestalotiopsis species were pathogenic to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of Pestalotiopsis are saprobes, while others are pathogenic or endophytic on living plant leaves and twigs [9]. Some Pestalotiopsis species have gained much attention in recent years as they produce many important secondary metabolites with potential use in medical applications and Cultivations were conducted at 30°C and pH 6.5 in 250-ml Xasks containing 100 ml of YEPX broth without shaking for 72 h. Biomass were measured as dry weight in the control of plant diseases [14,18,26]. No reports showed that Pestalotiopsis species were pathogenic to humans.…”
Section: Discussionmentioning
confidence: 99%
“…4-Oxo-4H-pyran-3-acetic acid (129) was isolated from the Chondracris rosea endophytic fungus Pestalotiopsis sp. HC02 (Zhang et al 2008). Pestalachlorides B (130) and C (131) are two chlorinated benzophenone derivatives found in the plant endophyte P. adusta.…”
Section: Miscellaneous Compoundsmentioning
confidence: 99%
“…HC02, a fungus residing in the gut of Chondracris rosea, along with 6-hydroxyramulosin (98). Among the above mentioned phytotoxins, compounds 96 and 97 notably inhibited radical growth of Echinochloa crusgalli with IC 50 values of 0.18 and 0.25 μM, respectively, and are thus comparable to 2-(2,4-dichlorophenoxy) acetic acid (IC 50 = 0.09 μM), which was used as a positive control (Zhang et al 2008). Chemical investigation of the endophyte Pestalotiopsis sp.…”
Section: Lactonesmentioning
confidence: 99%
“…Considerable chemical investigations of this genus have led to the discovery of secondary metabolites, such as terpenoids and polyketides with antifungal and cytotoxic activity [2][3][4]. In connection with our ongoing search for structurally diverse secondary metabolites from plant endophytes [5][6][7][8], we investigated the chemical constituents of an endophytic fungus Pestalotiposis guepinii, leading to the isolation and characterization of one new diphenyl ether derivative pestalotilide A (1, Figure 1), along with four known pyrone derivatives LL-P880γ (2) [9], LL-P880α (3) [9], 10-hydroxy-4-methoxy-6-pentyl-2H-pyran-2-one (4) [9], and 2-(4-oxo-4H-pyran-3-yl)acetic acid (5) [10]. This paper deals with the isolation and structure elucidation of pestalotilide A, as well as its cytotoxicity.…”
mentioning
confidence: 99%